Pelaksanaan Rekrutmen, Seleksi dan Penempatan Kerja pada Karyawan PT Midi Utama Tbk Cabang Medan - Roida Purba; Muhammad Ikhsan Harahap (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
PT. Midi Utama Indonesia Tbk Medana Branch, which operates in the retail sector in North Sumatra, must go through an effective recruitment, selection and placement process to select employees who meet the specified criteria. This research aims to understand how the recruitment, selection and placement of employees at PT. Midi Utama Indonesia Tbk Medan Branch in accordance with existing procedures, and to identify obstacles that may arise so that they can provide valuable recommendations for improvement. This research uses a qualitative approach by applying data collection methods through literature study, interviews and observation. The research results show that although the recruitment, selection and placement process at PT. Midi Utama Indonesia Tbk Medan Branch has been running well, but still requires evaluation to increase the effectiveness of each stage of the process.